SIKAP KETELADANAN GURU AGAMA ISLAM DALAM MEMBINA KARAKTER RELIGIUS PESERTA DIDIK DI SMA NEGERI 12 MAKASSAR - Tufail, Nur Fadli; Malli, Rusli; Sumiati, Sumiati (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
Ideally, education in school can produce students who not only have cognitive abilities or intellectual intelligence but are also accompanied by noble moral abilities, so that they can prepare children when they grow up, have strong character, and be useful for the homeland and nation. The aims of this research are 1) Analyzing the exemplary attitudes of Islamic Religious Education Teachers in developing the religious character of students at SMA Negeri 12 Makassar. 2) Finding a strategic picture of fostering the religious character of students at SMA Negeri 12 Makassar. 3) Analyze the factors inhibiting the development of students' religious character from the example of the Islamic Religious Education Teacher at SMA Negeri 12 Makassar. This research is descriptive qualitative. This research examines phenomena and events that occur in the lives of individuals and groups data collection instruments through observation and interviews. Data collection techniques consist of data reduction, data presentation, data collection, and verification. The research results prove that: 1). The teacher's exemplary attitude has a very important role in shaping the religious character of students in the context of Islamic education. a. Exemplary behavior (socializing), b. Exemplary in speaking (spoken), c. Exemplary appearance (dressing), d. Exemplary in worship (prayer), Effective strategies in developing religious character include: 1). Development strategies through classroom learning, 2). Development strategies through out-of-class learning, 3). Development Strategy Through Teacher and Parent Collaboration, 4). Strategy through reward and punishment advice, 3) Supporting and inhibiting factors are divided into: a. Supporting Factors, a). Exemplary Teacher, b). Facilities and Infrastructure, c). School Environment and d). Habituation Program. b. The inhibitor, a). Availability of support from educational institutions and legal policy makers, b). Lack of student attention, c). Technology